Ecocide, Climate Criminals and the Politics of Bushfires. (27th April 2022) - Walters, Reece
Abstract: Throughout the last thirty years bushfires or wildfires have increased globally with devastating impacts on ecosystems, human habitats and greenhouse gas emissions. The recording of unprecedented temperatures coupled with the warming of international oceans, and the melting of polar icecaps from anthropocentric climate change are major contributors to the increase of global wildfires that are forecasted to worsen unless urgent political intervention reduces greenhouse gas emissions. The state and corporate actors that enable widespread toxic emissions have been referred to as 'climate criminals' within discourses of ecocide and green criminology. This article adopts a green criminological lens to the emerging concept of 'ecocide' to examine political leaders and their mismanagement of devastating bushfires. Through a detailed interrogation of Australia's Royal Commission into National Natural Disaster Arrangements it traces the devastating Summer events of 2019/2020 and concludes that political inaction underpinned by fossil fuel economic priorities were instrumental in creating the contexts for a preventable environmental and human catastrophe.